Growth Relationships in Silver Fir Stands at Their Lower-Altitude Limit in Romania - Tudoran, Gheorghe Marian; Cicsa, Avram; Ciceu, Albert; Dobre, Alexandru-Claudiu (Forests, MDPI, MDPI AG, Grosspeteranlage 5, CH-4052 BASEL, SWITZERLAND, 2021)
This study presents the biometric relationships among various increments that is useful in both scientific and practical terms for the silvicultural of silver fir. The increments recorded in the biometric characteristics of trees are a faithful indicator of the effect of silvicultural work measures and of environmental conditions. Knowing these increments, and the relationships among them, can contribute to adaptations in silvicultural work on these stands with the purpose of reducing risks generated by environmental factors. We carried an inventory based on tree increment cores. The sample size was determined based on both radial increment and height increment variability of the trees. The sample trees were selected in proportion to their basal area on diameter categories. Current annual height increment (CAI(h)) was measured on felled trees from mean tree category. For CAI(h) we generated models based on the mean tree height. Percentages of the basal area increment and of form-height increment were used to compute the current annual volume increment percentage (PCAI(v)). For the mean tree, the CAI(h) estimated through the used models had a root-mean-square error (RMSE) of 0.8749 and for the current annual volume increment (CAI(v)) the RMSE value was 0.1295. In even-aged stands, the mean current volume increment tree is a hypothetical tree that may have the mean basal area of all the trees and the form-height of the stand. Conclusions: The diameter, height, and volume increments of trees are influenced by structural conditions and natural factors. The structures comprising several generations of fir mixed with beech and other deciduous trees, which have been obtained by the natural regeneration of local provenances, are stable and must become management targets. Stable structures are a condition for the sustainable management of stands.